2015
DOI: 10.4236/gsc.2015.52011
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Free Synthesis of Carboxylic Acids and Amide Analogs of CAPE (Caffeic Acid Phenethyl Ester) under Infrared Irradiation Conditions

Abstract: How to cite this paper: Martínez-Soriano, P.A., et al. (2015) AbstractA convenient and easy method is described for the formation of carboxamides from carboxylic acids and primary amines in solventless conditions using infrared (IR) light. Thus, under IR light, cinnamic acid derivatives and amines can produce yields ranging from 50% to 85% of the resulting amide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…(1) and derivatives (2-5) (Figure 1) has particularly increased, once they have showed several potential therapeutic activities, such as anti-inflammatory, antioxidant, antiviral, antibacterial, and antifungal. Likewise, multiple anticancer activities by inhibiting the growth of mammary (MCF-7) and prostatic (PC-3) neoplastic cells by inducing apoptosis (Gunia-Krzyżak et al, 2018;Pontiki et al, 2014;Jitareanu et al, 2013;Martínez-Soriano et al, 2015;Imai et al, 2019). Fonte: Jitareanu et al, (2013); Gunia-Krzyżak et al, (2018).…”
Section: Bioactivity Of Cinnamic Acid and Its Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) and derivatives (2-5) (Figure 1) has particularly increased, once they have showed several potential therapeutic activities, such as anti-inflammatory, antioxidant, antiviral, antibacterial, and antifungal. Likewise, multiple anticancer activities by inhibiting the growth of mammary (MCF-7) and prostatic (PC-3) neoplastic cells by inducing apoptosis (Gunia-Krzyżak et al, 2018;Pontiki et al, 2014;Jitareanu et al, 2013;Martínez-Soriano et al, 2015;Imai et al, 2019). Fonte: Jitareanu et al, (2013); Gunia-Krzyżak et al, (2018).…”
Section: Bioactivity Of Cinnamic Acid and Its Derivativesmentioning
confidence: 99%
“…In recent decades, it was found that CAD's from natural sources have anti-cancer, antioxidant and others related potential activity (Jitareanu et al, 2013;Martínez-Soriano et al, 2015;Zeng & Lai, 2019). Studies revealed that these biological activities were related to the cinnamoyl nucleus, present in the structure of this class of compounds, and hydroxyl groups, the latter being crucial for the elimination of free radicals and ROS, minimizing the oxidation of low-density lipoprotein (LDL) (Jitareanu et al, 2013;Martínez-Soriano et al, 2015).…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…In the last 10 years, interest in CA and its derivatives (esters, amides, aldehydes and alcohols) [ 5 ] has increased because of its many pharmacological activities, such as antituberculosis [ 6 , 7 , 8 , 9 ], antiviral [ 10 ], anticancer [ 11 , 12 , 13 , 14 , 15 , 16 ], mammary (MCF-7) and prostate (PC-3) inhibition, neoplastic cell growth, apoptosis inducement [ 17 , 18 , 19 ], anticholesterolemic [ 20 , 21 , 22 , 23 ], cardioprotective [ 24 ], antioxidant [ 25 , 26 , 27 , 28 ], anti-inflammatory [ 2 , 29 , 30 , 31 , 32 ], hepatoprotective [ 33 , 34 , 35 ], antidiabetic [ 36 , 37 , 38 ], antimalarial [ 39 ], anxiolytic [ 40 ], central nervous system depressant [ 41 ], neuroprotective [ 42 , 43 , 44 , 45 , 46 ], larvicidal agent [ 47 , 48 , 49 , 50 , 51 ], anti-leishmania [ 52 ], cosmetic […”
Section: Introductionmentioning
confidence: 99%
“…The following supporting information can be downloaded at: , Spectroscopic data of compounds [ 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 ].…”
mentioning
confidence: 99%